TINGKAT EFEKTIVITAS PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DAN PERTUMBUHANNYA SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KEDIRI TAHUN PERIODE 2014 - 2018 - Saleha, Dita Rindi; Solikah, Mar’atus (Universitas Nusantara PGRI Kediri, 2020)
One source of state revenue is from taxes. The Land and Building Tax (PBB) is one of the potential sources of tax revenue. Law number 28 of 2009 that changes the land and building tax management system from the center to a region that will increase regional income, so that it is expected to be able to contribute to finance the public interest and individual interests of the local community concerned. The tax revenue is still not optimal, so supervision is needed in its management.The purpose of this study was to analyze the level of effectiveness and growth of land and building tax revenues in rural and urban areas (PBB-P2) and their contribution to the Regional Original Revenues in Kediri Regency from 2014 to 2018.The approach in this research is quantitative with descriptive research techniques. The results of this study indicate that the level of receipt of Land and Building Taxes in Rural and Urban Areas (PBB-P2) from 2014 to 2018 to Regional Original Revenue (PAD) in Kediri Regency is more than 100% each year. It can be concluded that the receipt of Rural and Urban Land and Building Tax (PBB-P2) is classified as a very effective category. The growth rate has increased every year unless there is a decline in 2018. While the level of contribution to the original income of the region is less than 20.10%, so it falls into the category of less.